Prognostic value of the intraoperative D-dimer level in arterial blood in open reconstructive operations on the aortoiliac segment - Yu. А. Zaitseva; А. Ia. Bedrov; А. А. Moiseev; М. I. Kadinskaia; Iu. P. Kovalchuk; G. V. Rybakov; V. Iu. Veremiichuk; G. G. Khubulava (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to assess the prognostic value of D-dimer level in peripheral venous blood and arterial blood to the risk of developing complications in the short-term period after open reconstructive surgery on the aortoiliac segment.Methods and materials. The study included 89 patients who were determined the D-dimer level in peripheral venous blood, as well as arterial blood intraoperatively.Results. Statistically significant differences in the D-dimer level were established depending on the presence or absence of early postoperative complications.Conclusions. The intraoperative D-dimer level in arterial blood has a predictive ability in relation to the development of early postoperative complications.